A MicrocidadeTapira A Macroempresa VALEP e o Planejamento Tecnocrático Brasileiro - Cunha, Fernanda Martins (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1995)
This work has a general aim - the urban process planning as a political activity, seen in its concrete manifestations in a small town on the southwest of Minas Gerais. It is called Tapira and it has had about 2.000 inhabitants, from 1975 to our days. The research aims not only to demonstrate the political planning, but also to discover some ways by which it shows up concretely, emphasizing the popular reactions to w hat has been decided and put into practice by government. In disclosing the socio-political, economical and spacial problems ocurred at Tapira I w ill be able to known much better the up-to-date historic process in Brazil